Pengaruh Jenis Ekstrak Dan Beberapa Variasi Konsentrasi Zat Alelopati Alami Dalam Menghambat Perkecambahan Benih Dan Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Widiono, Fajar Kurnia Maulid; Kusbianto, Dwi Erwin; Arum, Ayu Puspita; Setiyono (Biospecies, 2026)
Cocoa is a strategic plantation commodity that contributes significantly to export-import activities, increasing the country's foreign exchange. However, the distribution of cocoa seeds is faced with the problem of recalcitrant seeds, which can be overcome by using natural allelopathic substances. Natural allelopathic plant extracts contain toxic compounds such as alkaloids, phenolics, and terpenoids which are effective in inhibiting germination. The purpose of this study was to determine the effect of the type of extract and the concentration of natural allelopathic substances in inhibiting the process of seed germination and growth of cocoa seedlings. This study used a factorial Completely Randomized Design (CRD). The first factor was the type of extract, namely cogongrass roots and tomato leaves. The second factor was the concentration of natural allelopathic substances, namely control, 4%, 6%, and 8%. Data were analyzed using the ANOVA (Analysis of Variance) test. If there was a significant difference between treatments, further testing was carried out using Duncan's multiple range test at the 5% level. The results of the study showed (1) the interaction between the type of extract and the concentration of natural allelopathic substances had a significant effect on the observed variables of germination power, vigor index, lethal concentration (LC50), plant growth rate, and number of leaves, with the best treatment being the cogongrass root extract at a concentration of 4%. (2) The effect of the type of natural allelopathic extract had a significant effect on the parameters of vigor index, plant growth rate, number of leaves, and stem diameter. (3) The effect of the concentration of natural allelopathic substances had no significant effect on any of the observed variables.